High temperature short time (HTST) camel milk pasteurization pilot plant - Tay T.T.; Chua Y.L. (Asian Research Publishing Network, 2023)
This paper reports on the design and fabrication of a High Temperature Short Time (HTST) camel milk pasteurization pilot plant. The objective of this project is to design and fabricate a low cost and practical camel milk pasteurization pilot plant which will work well in an agricultural setting in the Kingdom of Saudi Arabia. Fresh camel milk is a much sought after delicacies in the Arab world, usually sold directly by the farmer to the consumer without any further processing. However, this traditional method of milk handling has a few limitations where there is a possibility of milk contamination during handling, excess milk cannot be stored and the excess milk cannot be transported to other localities further away limiting the economic opportunities of the farmers. This pasteurization plant is based on High Temperature Short Time (HTST) continuous process where the raw camel milk will be indirectly heated to 72C via a heat exchanger. The milk temperature will be maintained at 72 C for 15s in a holding tube to kill most of the harmful microorganisms present in the milk. The pasteurized milk is then ready for consumption or can be refrigerated and stored for up to 21 days. With the introduction of this pasteurization pilot plant, it is hoped that the hygiene factor and the livelihood of the farmers will be improved where the camel milk can be stored longer and transported to stores safely to meet the demands of consumers. 2006-2015 Asian Research Publishing Network (ARPN).